Comparison of treatment of renal calculi by open surgery, percutaneous nephrolithotomy, and extracorporeal shockwave lithotripsy. Issue 6524 (29th March 1986) - Charig, C R; Webb, D R; Payne, S R; Wickham, J E
Abstract : This study was designed to compare different methods of treating renal calculi in order to establish which was the most cost effective and successful. Of 1052 patients with renal calculi, 350 underwent open surgery, 350 percutaneous nephrolithotomy, 328 extracorporeal shockwave lithotripsy (ESWL), and 24 both percutaneous nephrolithotomy and ESWL. Treatment was defined as successful if stones were eliminated or reduced to less than 2 mm after three months. Success was achieved in 273 (78%) patients after open surgery, 289 (83%) after percutaneous nephrolithotomy, 301 (92%) after ESWL, and 15 (62%) after percutaneous nephrolithotomy and ESWL. Comparative total costs to the NHS were estimated as 3500 pounds for open surgery, 1861 pounds for percutaneous nephrolithotomy, 1789 pounds for ESWL, and 3210 pounds for both ESWL and nephrolithotomy. ESWL caused no blood loss and little morbidity and is the cheapest and quickest way of returning patients to normal life.